2004
DOI: 10.2519/jospt.2004.34.11.662
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Experience and Specialty Certifications on Clinical Outcomes for Patients With Low Back Pain Treated Within a Standardized Physical Therapy Management Program

Abstract: Study Design: Secondary analysis of a randomized trial. Objectives: To examine the influence of experience and specialty certification on outcomes for patients with low back pain receiving a standardized manipulation or stabilization exercise intervention program. Background: Little research has examined the impact of therapist-related factors on the outcomes of clinical care for patients with low back pain. It is assumed that therapists with more clinical experience or specialty certification will achieve bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…It also appears that the intervention strategies proposed by the classification system can be applied effectively by physical therapists regardless of clinical experience. Whitman et al 124 found no difference in outcomes associated with therapists' years of experience in a group of patients with LBP who received manipulation or stabilization exercise interventions.…”
Section: 83mentioning
confidence: 99%
“…It also appears that the intervention strategies proposed by the classification system can be applied effectively by physical therapists regardless of clinical experience. Whitman et al 124 found no difference in outcomes associated with therapists' years of experience in a group of patients with LBP who received manipulation or stabilization exercise interventions.…”
Section: 83mentioning
confidence: 99%
“…Despite these findings, one cannot infer that patients cared for by expert clinicians will achieve superior outcomes when compared to the outcomes of patients treated by novice clinicians. 71,85 In fact, it has been demonstrated that expert clinicians are often resistant to changing their practice behaviors even when their treatment approaches have been disproven. 5 Hence, while clinical expertise is important, it is insufficient to assure optimal outcomes.…”
Section: Step 4 Incorporating Evidence Into Clinical Practicementioning
confidence: 99%
“…17,36,85 While some clinicians are quick to adopt change, many others are unfortunately resistant to change and rely predominantly on their clinical experience rather than incorporating evidence into their practice. 9 Although the volume and quality of emerging evidence in many areas of physical therapist practice is mounting rapidly, we acknowledge that there are still many areas where evidence is sparse and inconclusive.…”
Section: Step 4 Incorporating Evidence Into Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…For example, multiple theories exist to explain mechanisms of action and indications for techniques [32][33][34][35][36] . Issues also surround the effi cacy of techniques 37,38 , qualifi cations for performing manipulations 39 , and the lack of consistent defi nitions regarding manual therapy and manipulation in general 6,18-20, . These issues are very important, and debate on these topics should and will continue.…”
Section: Challenges Of the Taskmentioning
confidence: 99%